The mismatch between the language of training and language of teaching : Challenges faced by the selected Grade 2 Mathematics teachers - Julius, Lukas Homateni (JULACE: Journal of the University of Namibia Language Centre, 2020)
Although English is the dominant language of learning and teaching (LoLT) in many Namibian schools, the current Namibian Language in Education Policy (LiEP) prescribes that the Junior Primary Phase (Grades 0 to 3) learners in government schools should be taught in their first language (L1), and only later from Grade 4 onwards they can switch to English as LoLT. In training teachers, however, teacher training institutions such as the University of Namibia (UNAM) only use English as LoLT to train all the teachers, including those who will teach in the Junior Primary Phase. This becomes a challenge especially for content subject teachers who are trained in English and are expected to teach in a mother tongue other than English when they are formally employed in schools. This paper employed a qualitative interpretive approach to explore the challenges experienced by the selected Grade 2 Mathematics teachers who were trained at UNAM, regarding teaching Mathematics in the mother tongue. Data collection methods consisted of questionnaires and interviews with six Grade 2 Mathematics teachers who all graduated from UNAM. The data were analyzed inductively using the thematic content analysis approach. The key findings include that the preparation of Junior primary mathematics teachers was constrained by the mismatch between the language used to train them at UNAM and the language they are expected to use as a medium of instruction for actual teaching in schools, and the lack of prescribed materials for teaching Mathematics in the mother tongue. This study responds to the gap in mother tongue literacy teacher preparation and contributes to knowledge on how junior primary teachers should be prepared to teach all the subjects in the mother tongue as per the Namibian language policy.